DEFENSE MECHANISM OF CLARICE STARLING IN THE SILENCE OF THE LAMBS MOVIE (2007) DIRECTED BY JONATHAN DEMME:A SYCHOANALYTIC APPROACH - Hasim, Nur (2011)

(untitled)
The object of the study is a movie The Silence of The Lambs directed by Jonathan Demme. The study is to reveal how is defense mechanism reflected in The Silence of The Lambs movie directed by Jonathan Demme published in 2007. The objective of the study is to analyze the structural elements in the movie and to analiyze the anxiety of the main characters using psychoanalytic. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of The Silence of The Lambs and the secondary data source is biography of character. The method of collecting data are observation and library research. The technique of analyzing data is descriptive. Based on the analysis, the researcher draws two conclusions, first based on the structural analysis, Jonathan Demme wants to deliver moral message that about strength possibly be natural by the people considered to be by something that endanger, hence from the people self arise the Defense mechanism. From the structural analysis, it shows that each of the structural elements is interrelated to each other. Second, based on the psychoanalytic analysis, Jonathan Demme reflects defense mechanism is caused by the contradiction of his id, ego and superego which cause the be natural by the people considered to be by something that endanger, hence from the people self.